Competing under pressure: State anxiety, sports performance and assessment - Lundqvist, C. (2006)
Elevated levels of anxiety are a common response to stressful competitive sports situations, are known to moderate athletic performance and are referred to as an unpleasant emotional state associated with perceptions of situational threat. The empirical studies in this dissertation considered primarily psychometric, methodological and conceptual issues of relevance for the study of anxiety and sports performance. In Study I, athletes were followed across a full competitive season to explore patterns of inter- and intra-individual variability of anxiety and self-confidence in relation to performance. The findings imply intra-individual anxiety and self-confidence variability to affect performance differently than the specific intensity level and are discussed in relation to more stable personality dispositions such as private self-consciousness. Study II evaluated the psychometric properties of the 27-item Competitive State Anxiety Inventory-2 (CSAI-2) and alternative versions of this scale. General support for a 17-item version (CSAI-2R) was found, but there are also psychometric limitations future research needs to resolve. Study III investigated assessment of intensity and directional ratings on single anxiety items with reference to the conceptualisation of anxiety symptoms as interpreted on a debilitative-facilitative continuum. The findings question the importance and rationale of assessing anxiety direction and revealed serious concerns with assessment procedures and statistical techniques applied in previous research. These concerns were also supported in Study IV, which explored athletes` idiosyncratic experiences of debilitative and facilitative anxiety symptoms in terms of intensity and emotional valence. The findings are discussed and summarised in a model in order to increase conceptual clarity and provide implications for future research regarding anxiety and related emotional performance states.